2018
DOI: 10.3329/sja.v16i1.37428
|View full text |Cite
|
Sign up to set email alerts
|

Tribal womens involvement with pig farming in Bangladesh: an evidence of Moulvibazar district

Abstract: The study examined the profitability and factors affecting farm income from pig farming in Moulvibazar district of Bangladesh. A multistage sampling technique was followed to select 70tribal women entrepreneurs involved with pig farming. Primary data were collected through structured questionnaire and analyzed using descriptive statistics, independent sample t-test, benefit-cost analysis, and linear regression model. Average age of pig entrepreneurs was 39.47 years which indicates that they are young and agile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…As a result, all of them were involved in different low income jobs, conforming to the observations reported worldwide including Bangladesh [18,20]. Illiteracy is one of the constrains of pig industry since studies have shown that educated pig raisers can make more pro it than the uneducated ones [21,22]. Two third of the pig raisers were landless.…”
Section: Discussionsupporting
confidence: 75%
“…As a result, all of them were involved in different low income jobs, conforming to the observations reported worldwide including Bangladesh [18,20]. Illiteracy is one of the constrains of pig industry since studies have shown that educated pig raisers can make more pro it than the uneducated ones [21,22]. Two third of the pig raisers were landless.…”
Section: Discussionsupporting
confidence: 75%